Implementasi E-Journal sebagai Akselerasi Up-Date Referensi dan Fasilitas Pengenalan Evidence Based Nursing (EBN) di Institusi Pendidikan Keperawatan - Taukhit (LPPM STIKES NOTOKUSUMO YOGYAKARTA, 2013)
Along with the development of science and technology in education, especially learning the science of nursing, providing a challenge for teachers and students so that they can be used effectively in the learning in class nursing. Education recently started experiencing rapid growth and progress, including on nursing education to the critical learning and recognition of nursing actions that focuses on the scientific evidence (Evidence Based Nursing). One of the major breakthroughs to resolve the issue is the provision of e-journal. E-Journal is a scholarly journal that can be accessed through electronic documents in the form of computerized existence of the e-journal will make it easier for users to search for literature. In addition to the e-journal will also facilitate learning based on scientific evidence of nursing .e-Journal will allow access to scientific articles becomes easier and faster. Various advantages and convenience of the e-Journal, it is important to be developed in nursing education institutions as acceleration refernsi and up-date the introduction of evidence-based nursing (EBN).